Left atrial appendage sizing for percutaneous closure in virtual reality—a feasibility study - Heidari, Houtan; Kanschik, Dominika; Erkens, Ralf; Maier, Oliver; Wolff, Georg; Bruno, Raphael Romano; Werner, Nikos; Daniel Reinartz, Sebastian; Antoch, Gerald; Kelm, Malte; Zeus, Tobias; Jung, Christian; et al. (Frontiers in Cardiovascular Medicine, 2023)
The complex and highly variable three-dimensional anatomy of the left atrial appendage (LAA) makes planning and device sizing for interventional occlusion procedures (LAAC) challenging.Several imaging modalities (e.g. echocardiography, multi-slice computed tomography (MSCT)) are used for this purpose. Virtual reality (VR) is an emerging imaging technique to immerse into a three-dimensional left atrium and appendage, offering unprecedented options of visualization and measurement. This study aimed to investigate the feasibility, accuracy and reproducibility of visualizing the LAA in VR for preprocedural planning of LAAC.Twenty-one patients (797 years, 62% male) who underwent LAAC at University Hospital Düsseldorf were included in our study. A dedicated software generated three-dimensional VR models from preprocedural MSCT imaging data. Conventional measurements of LAA dimensions (ostium, landing zone and depth) using a commercially available software were compared to measurements in VR: MSCT and VR ostium min. (r = 0.93), max. (r = 0.80) and mean (r = 0.88, all p<0.001) diameters as well as landing zone (LZ) min. (r=0.84), max. (r=0.86) and mean diameters (r=0.90, all p<0.001) showed strong correlations. Three-dimensional orientation was judged superior by physicians in VR compared to MSCT (p<0.05).Virtual reality visualization of the left atrium and appendage based on MSCT data is feasible and allows precise and reproducible measurements in planning of LAA occlusion procedures with enhanced 3D orientation. Further studies need to explore additional benefits of threedimensional visualization for operators in preprocedural planning.